Conservation value of constructed reedbeds - Athorn, Marie (2018)
Natural reedbed habitat in the UK has suffered severe declines in the last few centuries. With only 5,000 ha remaining and much of what remains is highly fragmented and degraded. The loss and fragmentation of reedbed habitat in the UK has had a profound effect on the species associated with it. Constructed reedbeds are artificial wetlands dominated by Phragmites australis designed to treat wastewater. They have been widespread in the UK because they are perceived to be a green solution, but their conservation value has never been assessed. This project aims to determine how they contribute to biodiversity. This study surveyed 24 sites, 12 constructed sites paired to 12 natural sites, for small mammals, moths and stem-dwelling invertebrates. Results show that there is no difference between constructed and natural sites. The indication is that constructed reedbeds, despite their small size, young age and contamination, are just as diverse as natural reedbeds. The implications of this for reedbed and wetland conservation are potentially substantial. There are over 1,000 constructed reedbeds in the UK that are just as diverse as their natural equivalents, which could provide connectivity across unsuitable agricultural and urban landscapes.